Genetic studies for improvement of spike characters in bread wheat - B, Annapurna; Bankar, DN; Patil, R M; Khade, V M; Surve, VD; Chavan, AM; Bagwan, JH; Taware, S P; Honrao, B K; Misra, S C (Journal of Cereal Research, 2011)
Five generations each, of the three crosses viz. MACS2496 × Pavon 1 (C1), MACS2496 × Mexico wheat (C2) and Pavon1 × K9644 (C3), were evaluated for spike length (cm), number of spikelets per spike, number of grains per spike and 1000 grain weight (g). The generations involving P1, P2, F1, F2 and F3 were evaluated in a randomized block design. The 5 parameter model suggested by Jinks and Jones (1958) was used for generation mean analysis. Heritability and genetic advance were also estimated. The computation of genetic advance revealed that combinations MACS2496 x Pavon1 and MACS2496 x Mexico wheat were beneficial for the improvement of 1000 grain weight.